Colorado water, November 1988 - Colorado Water Resources Research Institute, author (Colorado State University. Libraries, 1988)
Newsletter of the Colorado Water Resources Research Institute.
Keywords: Water resources development -- Colorado; Water-supply -- Colorado; Water use -- Colorado; Water-supply -- Management -- Colorado